2014
DOI: 10.1097/iop.0b013e31829f3a57
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Metastasis From Hepatocellular Carcinoma

Abstract: A series of 6 consecutive cases of orbital metastasis from hepatocellular carcinoma (HCC) were reported in the last 5 years. All patients were men. The age of patients ranged between 47 and 70 years. Four patients presented with recent onset of unilateral proptosis, 1 patient presented with inflammatory manifestations, and 1 patient presented with unilateral ptosis. Pain was present in 4 patients. Three patients had a previous history of HCC, while the orbital affection was the first manifestation of the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…The current study conducted a review of the relevant Chinese- and English-language medical literature, and identified 39 cases of HCC metastasis to the head reported since 2009 ( Table I ) ( 4 , 7 – 35 ). Of these 39 patients, 11 exhibited peri-orbital metastasis similar to that of the present patient ( Table II ) ( 4 , 17 19 , 25 , 30 ). Of the 11 cases with HCC metastasis to the orbit published since 2009, all were male (with the exception of no gender being reported in one case)e, five exhibited invasion from the right side, only two patients demonstrated peri-orbital invasion combined with cerebral invasion, yet cerebral invasion also occurred in the present case.…”
Section: Discussionsupporting
confidence: 61%
“…The current study conducted a review of the relevant Chinese- and English-language medical literature, and identified 39 cases of HCC metastasis to the head reported since 2009 ( Table I ) ( 4 , 7 – 35 ). Of these 39 patients, 11 exhibited peri-orbital metastasis similar to that of the present patient ( Table II ) ( 4 , 17 19 , 25 , 30 ). Of the 11 cases with HCC metastasis to the orbit published since 2009, all were male (with the exception of no gender being reported in one case)e, five exhibited invasion from the right side, only two patients demonstrated peri-orbital invasion combined with cerebral invasion, yet cerebral invasion also occurred in the present case.…”
Section: Discussionsupporting
confidence: 61%
“… 4 , 14 Osteoclastic lesions can be found in metastasis from HCC which varies from bone notching and thinning to bone erosion. 24 Orbital metastatic lesions can be extraconal or intraconal. They may range from a diffuse infiltrative pattern to a focal lesion.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 However, in orbital metastasis, particularly from HCC, it can be as high as 50%. 5,6 Ocular signs from orbital metastasis secondary to HCC often present earlier than that of primary cancer. 7 Approximately 80-90% of patients with HCC have chronic liver disease and cirrhosis caused by alcoholic liver disease and chronic infection with the hepatitis B and C viruses.…”
Section: Discussionmentioning
confidence: 99%